CARDIOVASCULAR ASSESSMENT OF PRIMARY CARE USERS: RESIDENTS’ PERCEPTION (Fiep Bulletin - online, 2025)
Introduction: Within the scope of Primary Health Care, one of the main health conditions affected by users are Chronic Non-Communicable Diseases (NCDs), mainly High Blood Pressure. Objective: To evaluate multidisciplinary family health interventions on the cardiovascular condition of Primary Health Care users from the perspective of residents. Methods: This is an exploratory, descriptive and quantitative research. Concentrated on the perception of PSF residents, who have been working for 1 (one) month in community projects at the Basic Health Unit (UBS), located in the south zone of the city of Teresina-PI. The study involved 03 (three) categories: Physical Education, Nursing and Nutrition and 15 (fifteen) users. Results: The eMulti Work was fundamental to achieving success in the interventions carried out by professionals from the RMSF/UESPI team since the beginning of the program. Initially, users were able to perform the training session proposed by Physical Education Professionals, obtaining the measurement of maximum HR (100/92bpm), BP (50/140mmHg) and DP (14,000mmHg/12,320mmHg), before and after the training by nurses and participating in the lecture on nutritional guidelines developed by the nutritionist. Recognizes that FC (p
Keywords: Multidisciplinary team; academic training; family health strategy